Museum Seni Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Agnes Yunus Agaperi S; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pekanbaru is a famous city for the diversity of society who inhabit this city. The plural of society produce a diversity of culturally diverse artistic heritage anyway, so it takes a container to preserve the artistic and cultural heritage that heritage is not lost and remains a hallmark of the Pekanbaru city. Art Museum which is a vehicle to capture and document the activities and events and historic objects, especially with regard to art and culture is the answer of the need for the container to preserve the heritage of art and culture in the city is auspicious. In designing an art museum in Pekanbaru, the design approach is more emphasis on the application of the principle of Tropical Architecture with the aim that the academy is able to answer a variety of issues related to tropical climate that houses which is place on Pekanbaru. Some of the principles of TropicalArchitecture that will be applied in the design is: (1) Orientation of the building; (2) Optimization of natural aeration; (3) The use of the stage; (4) Shape slanted roof conditions: (5) vegetation. With the complexity of climate-relatd issue in Pekanbaru, then it would be better if this Pekanbaru Artmuseum design with the approach of Tropical Architecture. So that by applying the principles of Tropical Architecture in this design is expected to generate a good art museum for users and arouse people's desire to re-apply the principles of Tropical Architecture in designing various kinds of buildings in Indonesia, especially in the Pekanbaru city.Keywords: Art Museum, Tropical Architecture, Principle.